Psychological motivators of bystanders to help people injured in traffic Accidents: A qualitative content analysis - Mohammad Jafar Sepahvand; Kian Nourozi; Hamidreza Khankeh; Farahnaz Mohammadi-Shahboulaghi; Masoud Fallahi-Khoshknab (Elsevier, 2024)
Background: In many countries, the necessary support for bystanders is not provided. Despite the problems and complications caused by participation with the help of bystanders, psychological motivations and internal drivers will help them participate. The present study was conducted in order to identify the psychological motivators of bystanders to help in traffic accidents. Methods: This qualitative study is part of a larger study, a doctoral dissertation in nursing. study was conducted using the qualitative description method in Iran in 2022. Sampling was purposeful and then theoretical. Data was collected through semi-structured interviews with 15 participants, including 10 male and 5 female participants. The data was analyzed using a conventional content analysis approach and constant comparison simultaneously, as recommended by Corbin and Strauss (2015). Using these two approaches at the same time helps to code the data, determine subcategories and categories, identify patterns and themes, understand the complexity of the human experience, develop new hypotheses and theories, enhance validity and reliability, and facilitate communication and collaboration with colleagues, stakeholders, and non-experts. MAXQDA 2010 software was used to assist in data analysis. Results: Six concepts-feeling of responsibility, spiritual beliefs, feeling of pity, self-sacrificing, prevention of guilty conscience, and the feeling of becoming a hero-were identified as the subcategory of psychological motivators and the most important psychological motivators among the bystanders. Conclusion: Bystanders will not help until they feel responsible. A feeling of responsibility can cause bystanders to self-sacrifice to prevent a guilty conscience. Having spiritual beliefs, a feeling of responsibility, and a sense of heroism can increase the feeling of responsibility and motivation of bystanders to help. It is suggested that ways of increasing the feeling of responsibility and other psychological motivators and the role of education, skill, experience, and legal obstacles in bystanders should be investigated in future studies.